BUSINESS SUSTAINABILITY DETERMINANTS IN MSMES MEMBERS OF THE WASTE RECYCLING COOPERATIVE, CENTRAL BOGOR - Asep Sofwan Munandar; Awa Awa (Jurnal Visionida, 2026)
The problem of waste, especially plastic, has become a crucial global environmental challenge due to its inherent difficulty in decomposing naturally. Despite the enormous potential for waste reduction and the aesthetic value of products, the long-term business sustainability of MSMEs still faces serious obstacles. This study aims to analyze and measure the influence of green financial literacy and circular entrepreneurship on business sustainability through green financial performance, using a case study of MSMEs as members of a waste recycling cooperative in Central Bogor. This research method uses a quantitative approach with a causal associative method. The population is all MSMEs registered as active members of the waste recycling cooperative in Central Bogor, amounting to 80 people. The sampling technique used is saturated or census sampling. Data analysis was conducted using the Variance-Based Structural Equation Modeling (VB-SEM) approach. The results show that the coefficient of determination model R2 path 1 is 0.501 and R2 path 2 is 0.755. Green financial literacy and circular entrepreneurship have a positive and significant effect on green financial performance and business sustainability. In addition, green financial performance also has a positive and significant effect on business sustainability and mediates the influence of green financial literacy and circular entrepreneurship on business sustainability